Lithium-sulfur battery

The lithium sulfur battery design, featuring a porous carbon-sulfur composite positive electrode and a tailored electrolyte system, enhances electrical conductivity and sulfur retention, resulting in improved discharge capacity, Coulomb efficiency, and cycle characteristics.

JP7660398B2Active Publication Date: 2025-04-11ASAHI KASEI KOGYO KABUSHIKI KAISHA +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021038121
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-10
Publication Date
2025-04-11
Estimated Expiration
2041-03-10

AI Technical Summary

Technical Problem

Lithium sulfur batteries face challenges with low capacity due to poor electrical conductivity of sulfur-based positive electrode materials, and issues with sulfur loss during charging and discharging, leading to decreased battery capacity and insufficient cycle characteristics.

Method used

A lithium sulfur battery design incorporating a positive electrode made from a composite material of porous carbon with a high nitrogen content, sulfur, and a specific electrolyte system, including a sulfonyl group solvent and a fluorine-based solvent, to enhance electrical conductivity and sulfur retention.

Benefits of technology

The proposed battery achieves a significant increase in discharge capacity, high Coulomb efficiency, and excellent cycle characteristics, addressing the limitations of previous lithium sulfur battery technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660398000005
    Figure 0007660398000005
  • Figure 0007660398000006
    Figure 0007660398000006
  • Figure 0007660398000007
    Figure 0007660398000007
Patent Text Reader

Abstract

To provide a lithium-sulfur battery which has a high first-time discharge capacity, a high first-time coulombic efficiency, and an excellent cycle property.SOLUTION: A lithium-sulfur battery comprises: a positive pole comprising a composite material comprising a porous carbon material and sulfur, the porous carbon material having a nitrogen content of 0.3 mass% or more, a specific surface area obtained by a BET method in a nitrogen adsorption-desorption method of 1000 m2 / g or more, and a pore volume obtained by quenched solid density functional theory (QSDFT) of 0.45 cm3 / g or more; a negative pole comprising lithium; and an electrolytic solution comprising a first solvent having a sulfonyl group, a second solvent, the second solvent being a fluorine-based solvent, and a lithium-containing electrolyte.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium-sulfur battery having a positive electrode active material containing sulfur, a negative electrode active material containing lithium, and an electrolyte. [Background technology]

[0002] Lithium ion secondary batteries use an organic electrolyte solution of lithium salt as a non-aqueous electrolyte, are lightweight and have a high energy density, and are used as power sources for mobile phones and notebook computers, and are expected to be used as power sources for mobile vehicles such as hybrid cars in the future. Therefore, in recent years, there has been an increasing demand for batteries with higher capacity density and low cost.

[0003] Generally, metal oxides containing Co, Ni, Mn, Fe, or the like and Li are used as the positive electrode active material of lithium-ion secondary batteries, but in recent years, lithium-sulfur batteries have been developed that use sulfur, which has an extremely high theoretical capacity density and is low cost, as the positive electrode active material instead of these positive electrode active materials. Lithium-sulfur batteries are secondary batteries that use a sulfur-based compound as the positive electrode active material and a material, such as silicon, in which insertion and desorption of alkali metals such as lithium or metal ions such as lithium ions occurs, as the negative electrode active material. The sulfur redox reaction is reversible, and because there are many reactive electrons, the battery has a theoretical capacity of 1672 mAh / g, which is approximately 10 times that of metal oxide positive electrodes.

[0004] However, the positive electrode active material made of lithium and sulfur has the following problems. First, the positive electrode active material, which is made up of lithium and sulfur, has poor electrical conductivity, and can only exchange electrons near the surface. This reduces the utilization rate of sulfur involved in the electrochemical redox reaction, resulting in low battery capacity.

[0005] In addition, the reaction during charging and discharging produces the compound Li2S x(wherein x is 4 to 8) dissolves into the electrolyte, causing the loss of sulfur present on the positive electrode, resulting in a decrease in the capacity of the lithium-sulfur battery. x It is desirable to stop the dissolution of the

[0006] As a technique for solving the above-mentioned problems, a technique for compounding a carbon material, which is a conductive material, with sulfur has been proposed. The inventors have discovered a technique for producing a composite made of activated carbon containing 31% sulfur by heating sulfur and activated carbon at 155°C for 5 hours, thereby melting and diffusing the sulfur into the carbon material (see Non-Patent Document 1).

[0007] Furthermore, the present inventors have discovered a technique for compositing a nitrogen-containing carbon material with sulfur by chemically activating the nitrogen-containing porous carbon material as a carbon material and melting and diffusing sulfur into the obtained carbon material (see Patent Document 1). In the technology disclosed in Patent Document 1, a "composite of carbon material and sulfur" obtained by using a nitrogen-containing porous carbon material has a large sulfur loading amount of 54 to 62 mass %, and when this is used as a positive electrode active material of a lithium-sulfur battery, it has the advantages of having a large capacity per sulfur mass and a large capacity per composite containing sulfur and carbon material, and excellent cycle characteristics.

[0008] Patent Document 2 discloses a lithium-sulfur battery using a positive electrode made of sulfur / Ketjen black and using sulfolane as a solvent. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2018-39685 A [Patent Document 2] Republished No. 2019 / 049826 [Non-patent literature]

[0010] [Non-Patent Document 1] Progress in Natural Science: Materials International, 25, 612-621(2015) Summary of the Invention [Problem to be solved by the invention]

[0011] However, a lithium-sulfur battery using the composite described in Non-Patent Document 1 as a positive electrode active material has a relatively large capacity per mass of sulfur, but has a problem in that the capacity per mass of the composite containing sulfur and a carbon material is low because the sulfur content is 31 mass%. The composite obtained by the technique described in Patent Document 1 has a larger amount of sulfur supported than the composite obtained by the technique described in Non-Patent Document 1, and when this is used as a positive electrode active material in a lithium-sulfur battery, the capacity per sulfur mass and the capacity per composite containing sulfur and a carbon material are large. However, there are problems in that the first coulombic efficiency is low and the cycle characteristics are insufficient.

[0012] The technology described in Patent Document 2 has a problem in that the first discharge capacity at 0.1 C is about 800 mAh / g as shown in Figures 12, 17, 22, and 24, and the discharge capacity is low.

[0013] In view of the above-mentioned problems in the conventional technology, an object of the present invention is to provide a lithium-sulfur battery having a large first discharge capacity, a high first coulombic efficiency, and excellent cycle characteristics. [Means for solving the problem]

[0014] As a result of intensive research into achieving the above-mentioned object, the present inventors have found that a lithium-sulfur battery having a porous carbon material having a specific structure, a positive electrode containing sulfur, a negative electrode containing lithium, and a specific electrolyte solution can solve the above-mentioned problems in the conventional technology, and have thus completed the present invention.

[0015] That is, the present invention is as follows. [1] A positive electrode including a composite material including a porous carbon material and sulfur, a negative electrode including lithium, a first solvent having a sulfonyl group, a second solvent which is a fluorine-based solvent, and an electrolyte including a lithium-containing electrolyte, wherein the porous carbon material has a nitrogen content of 0.3 mass% or more and a specific surface area obtained by the BET method of a nitrogen adsorption / desorption method of 1000 m 2 / g or more, and the pore volume obtained by quenched solid phase density function method (QSDFT) is 0.45 cm 3 / g or more, and the first solvent is 1.0 to 8.0 mol per 1 mol of lithium in the lithium-containing electrolyte.

[0016] [2] The lithium-sulfur battery according to [1], wherein the first solvent is one or more solvents selected from the group consisting of sulfolane, 3-methylsulfolane, ethyl methyl sulfone, and ethyl isopropyl sulfone.

[0017] [3] The lithium-sulfur battery according to [1] or [2], wherein the second solvent is one or more solvents selected from fluoroethylene carbonate (FEC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)-propane (HFE).

[0018] [4] The lithium-sulfur battery according to any one of [1] to [3], wherein the second solvent is 0.1 to 5 mol per 1 mol of the first solvent.

[0019] [5] The lithium-sulfur battery according to any one of [1] to [4], wherein the sulfur content in the composite material is 35 to 90 mass %.

[0020] [6] The lithium-sulfur battery according to any one of [1] to [5], wherein the porous carbon material is produced by activating a nitrogen-containing carbon material, and a reduction rate of the nitrogen content defined by the following formula (I) is 30 to 99 mass %. Reduction rate of nitrogen content (mass%) = ((BA) / B) x 100 (I) (In formula (I), A is the nitrogen content (mass%) in the porous carbon material measured by XPS, and B is the nitrogen content (mass%) in the nitrogen-containing carbon material measured by XPS.)

[0021] [7] The lithium-sulfur battery according to [6], wherein the nitrogen-containing carbon material has a nitrogen content of 2 to 45 mass %.

[0022] [8] The lithium-sulfur battery according to [6] or [7], wherein the activation is chemical activation. Effect of the Invention

[0023] According to the present invention, it is possible to provide a lithium-sulfur battery having a large first discharge capacity, a high first coulombic efficiency, and excellent cycle characteristics. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is an explanatory diagram of a method for calculating heights from the peaks (H1 and H2) and height from the minimum value M (L) from the laser Raman spectrum of a porous carbon material. [Diagram 2] 1 is a graph showing thermogravimetric (TG) analysis results when measuring a composite material containing a porous carbon material and sulfur, and sulfur alone, as described in an example. [Diagram 3] 1 is a laser Raman spectrum of the porous carbon material obtained in Example (Production of Porous Carbon Material). [Figure 4] FIG. 2 is a pore distribution diagram obtained by a slit model of the quenched solid-state density functional method (QSDFT) of the nitrogen adsorption / desorption method in the porous carbon material obtained in the Example [Production of porous carbon material]. [Diagram 5]1 shows first charge / discharge curves for Examples 1 to 5 and Comparative Example 1. [Figure 6] 1 is a graph showing cycle characteristics of Examples 1 to 4, Comparative Example 1, and Comparative Example 2. [Figure 7] 1 is a graph showing cycle characteristics of Examples 3, 6, and 7. [Figure 8] 1 shows the first, second, and 30th charge / discharge curves in Examples 3, 8, and 9. [Figure 9] 1 is a graph showing cycle characteristics of Examples 3, 8, and 9. [Figure 10] 1 shows cyclic voltammetry (CV) of Comparative Example 1. [Figure 11] 1 shows cyclic voltammetry (CV) of Example 1. [Figure 12] 1 shows cyclic voltammetry (CV) of Example 2. [Figure 13] 1 shows cyclic voltammetry (CV) of Example 3. [Figure 14] 1 shows cyclic voltammetry (CV) of Example 4. [Figure 15] 1 shows cyclic voltammetry (CV) of Example 5. [Figure 16] 1 shows cyclic voltammetry (CV) of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Hereinafter, an embodiment of the present invention (hereinafter simply referred to as "the present embodiment") will be described in detail with reference to the drawings as necessary. The present embodiment is an example for explaining the present invention, and the present invention is not limited to the embodiment. In other words, the present invention can be modified in various ways without departing from the gist of the present invention.

[0026] The lithium-sulfur battery of this embodiment will be described below. The lithium-sulfur battery of this embodiment has a positive electrode, a negative electrode, and an electrolyte, and typically also has a separator and an exterior body.

[0027] <Positive electrode> The positive electrode of the present embodiment includes a composite material containing a porous carbon material and sulfur.

[0028] (Porous carbon materials) The porous carbon material used in this embodiment has a nitrogen content of 0.3% by mass or more and a specific surface area of ​​1000 m2 obtained by the BET method using nitrogen adsorption and desorption. 2 / g or more, and the pore volume obtained by quenched solid phase density function method (QSDFT) is 0.45 cm 3 / g or more. Since the porous carbon material has the above-mentioned configuration, a lithium-sulfur battery using a composite material containing the porous carbon material and sulfur in a positive electrode can achieve high coulombic efficiency and discharge capacity per sulfur mass, as well as excellent cycle characteristics.

[0029] A preferred method for producing the porous carbon material used in this embodiment includes a method having a step of producing a nitrogen-containing carbon material and a step of activating the nitrogen-containing carbon material, for example, by chemical activation. After the activation, for example, by chemical activation, a step of heat treatment in an inert gas may be included.

[0030] Although it is unclear why a lithium-sulfur battery using a porous carbon material exhibits excellent characteristics, the present inventors speculate as follows, although the present invention is not limited to this speculation in any way. When pores are formed by activating a nitrogen-containing carbon material, for example by chemical activation and heat treatment, the nitrogen portion is preferentially removed, and thus micropores are preferentially formed. It is believed that the combined effects of the immobilization of sulfur in the generated micropores to suppress elution and increase the amount of sulfur available for electron transfer, as well as the immobilization of sulfur to the remaining nitrogen functional groups, result in excellent effects when the composite material of the present embodiment is used as the active material for the positive electrode of a lithium-sulfur battery.

[0031] In this specification, the "pore" in "pore volume" is uniquely determined by quenched solid state density function method (QSDFT), and in a pore distribution diagram obtained by this method, pores with a pore diameter of 2 nm or less are called micropores, pores with a pore diameter of more than 2 nm and not more than 50 nm are called mesopores, and pores with a pore diameter of more than 50 nm are called macropores.

[0032] The porous carbon material is produced by activating a nitrogen-containing carbon material (for example, by chemical activation), and the reduction rate of the nitrogen content defined by the following formula (I) is preferably 30 to 99 mass %.

[0033] Reduction rate of nitrogen content (mass%) = ((BA) / B) x 100 (I) (In formula (I), A is the nitrogen content (mass%) in the porous carbon material measured by XPS (X-ray photoelectron spectroscopy), and B is the nitrogen content (mass%) in the nitrogen-containing carbon material measured by XPS.) Specific measurement methods are as described in the Examples.

[0034] [Nitrogen-containing carbon material and manufacturing process for nitrogen-containing carbon material] The nitrogen-containing carbon material used in the method for producing a porous carbon material is a carbon material that contains nitrogen.

[0035] The nitrogen-containing carbon material can be produced by, for example, a method of polymerizing a low molecular weight nitrogen-containing organic compound as a raw material and carbonizing the resulting polymer, a method of performing chemical vapor deposition (CVD) using a low molecular weight nitrogen-containing organic compound as a raw material, a method of impregnating or reacting a polymer with a low molecular weight nitrogen-containing organic compound and then carbonizing the polymer, a method of carbonizing a nitrogen-containing natural product, and a method of performing post-treatment such as ammonia treatment and / or ammoxidation treatment on a carbonized product.

[0036] Specifically, nitrogen-containing carbon materials can be produced by a method of chemical vapor deposition of nitrogen-containing organic compounds such as pyrrole, acetonitrile, and 2,3,6,7-tetracyano-1,4,5,8-tetraazanaphthalene; a method of carbonizing melamine resin, urea resin, aniline resin, polyacrylonitrile, azulmic acid, melem polymer, polypyrrole, polyimide, etc., or precursors obtained by mixing these with other polymers; a method of carbonizing beans, etc.; and a method of reacting ammonia gas and an oxygen-containing gas with a carbon material such as activated carbon.

[0037] When various organic compounds are used as raw materials and subjected to thermal history as described above, it is preferable to give them a thermal history of 600° C. or higher.

[0038] The nitrogen-containing carbon material is preferably a nitrogen-containing carbon material having a high nitrogen content. The nitrogen content in the nitrogen-containing carbon material is measured by CHN analysis. The specific measurement method is as described in the Examples.

[0039] In this embodiment, the nitrogen content of the nitrogen-containing carbon material is preferably 2 to 45% by mass. The lower limit of the nitrogen content is more preferably 3% by mass or more, even more preferably 5% by mass or more, and even more preferably 10% by mass or more. The upper limit of the nitrogen content is more preferably 40% by mass or less, even more preferably 35% by mass or less, and even more preferably 30% by mass or less. When a nitrogen-containing carbon material having a nitrogen content of 2% by mass or more is used, micropores are likely to develop. A nitrogen-containing carbon material having a nitrogen content of 45% by mass or less is likely to develop a carbon structure.

[0040] The nitrogen content of the nitrogen-containing carbon material can be controlled by appropriately selecting the nitrogen content of the polymer used as the raw material. For example, a method for producing a nitrogen-containing carbon material having a high nitrogen content can be exemplified by carbonizing a polymer having a high nitrogen content.

[0041] Specific examples of the nitrogen-containing carbon material include those produced by carbonizing azulmic acid, melem polymer, and polyacrylonitrile, and a preferred nitrogen-containing carbon material is that produced by carbonizing azulmic acid. Azurumic acid is a polymer obtained by polymerizing hydrocyanic acid or hydrocyanic acid oligomers. Hydrocyanic acid oligomers are dimers or higher of hydrocyanic acid.

[0042] The conditions for the carbonization of the polymer include, for example, carrying out a heat treatment under an inert gas atmosphere using a rotary furnace, a tunnel furnace, a tubular furnace, a box furnace, a fluidized bed furnace, etc. The temperature for the heat treatment is not particularly limited, but is preferably 600 to 1200°C, more preferably 700 to 1000°C, and further preferably 750 to 900°C.

[0043] The inert gas is not limited to the following gases, but may be, for example, nitrogen, argon, helium, neon, or other inert gases. The inert gas atmosphere may be under reduced pressure, that is, a pressure environment lower than atmospheric pressure. Among these, it is preferable to use nitrogen gas as the inert gas. The inert gas atmosphere may be stationary or flowing, but it is preferable that the inert gas is flowing. The oxygen concentration in the inert gas is preferably 5% or less, more preferably 1% or less, and even more preferably 1000 ppm or less.

[0044] The time for the carbonization treatment is preferably from 10 seconds to 100 hours, more preferably from 5 minutes to 10 hours, even more preferably from 15 minutes to 5 hours, and even more preferably from 30 minutes to 2 hours.

[0045] When an inert gas is used, the pressure during the carbonization treatment is preferably 0.01 to 5 MPa, more preferably 0.05 to 1 MPa, even more preferably 0.08 to 0.3 MPa, and even more preferably 0.09 to 0.15 MPa.

[0046] The nitrogen-containing carbon material produced by the above process is preferably a material having a main peak at a diffraction angle (2θ) position of 22.5 to 26.8° derived from the (002) plane in an X-ray diffraction diagram (XRD) obtained using CuKα radiation as an X-ray source, and also preferably has a weak peak observed at a position of 43.0 to 46.0°, usually at a position of 44.0 to 45.5°.

[0047] Nitrogen-containing carbon materials may contain other atoms besides carbon and nitrogen, such as oxygen and hydrogen.

[0048] [Step of activating nitrogen-containing carbon material to produce porous carbon material] Next, a process for producing a porous carbon material by activating a nitrogen-containing carbon material will be described. Activation is a treatment for making a nitrogen-containing carbon material porous.

[0049] In the activation step of the nitrogen-containing carbon material, chemical activation is particularly preferred from the viewpoint of facilitating the production of a porous carbon material having a large specific surface area, high microporosity, and large pore volume.

[0050] The chemical activation step is carried out by mixing the nitrogen-containing carbon material with a chemical and heat-treating the mixture. The chemical used in the chemical activation step refers to a chemical that is solid at 25° C. and atmospheric pressure, as well as its hydrate and aqueous solution. The chemicals are not particularly limited, but examples thereof include alkali metal hydroxides such as potassium hydroxide and sodium hydroxide, alkali metal carbonates such as potassium carbonate and sodium carbonate, alkali metal sulfates such as potassium sulfate and sodium sulfate, zinc chloride, calcium chloride, potassium sulfide, phosphoric acid, etc., and aqueous solutions or hydrates thereof. One of these may be used alone, or two or more may be mixed and used.

[0051] From the viewpoint of controlling the specific surface area and pore volume within the desired range, the chemical activation is preferably alkali activation using a chemical containing an alkali metal, specifically, activation using potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, etc.

[0052] In the chemical activation step, the amount of chemical used relative to the nitrogen-containing carbon material is not particularly limited, but the chemical / nitrogen-containing carbon material (mass ratio) is preferably 0.1 to 10. The lower limit of the chemical / nitrogen-containing carbon material (mass ratio) is more preferably 0.3 or more, and even more preferably 0.5 or more. The upper limit of the chemical / nitrogen-containing carbon material (mass ratio) is more preferably 5 or less, and even more preferably 3 or less. When the chemical / nitrogen-containing carbon material (mass ratio) is 0.1 or more, pores are sufficiently developed, and when it is 10 or less, overactivation can be prevented and destruction of the pore walls can be suppressed.

[0053] The atmosphere for chemical activation is preferably an inert gas atmosphere, such as nitrogen, argon, helium, and neon.

[0054] The chemical activation treatment is not particularly limited, but is carried out at a temperature of, for example, 500 to 1100° C., more preferably 600 to 1000° C., and even more preferably 700 to 900° C. When the temperature of the chemical activation treatment is 500° C. or higher, the activation proceeds sufficiently, and when the temperature is 1100° C. or lower, the excessive progression of the activation can be suppressed and the occurrence of corrosion of the activation device can be prevented.

[0055] The time for the chemical activation treatment is not particularly limited, but is preferably 10 minutes to 50 hours, more preferably 30 minutes to 10 hours, and further preferably 1 to 5 hours.

[0056] The pressure for the chemical activation treatment is usually normal pressure, but it is also possible to carry out the treatment under increased or reduced pressure.

[0057] As the activation furnace, a rotary furnace, a tunnel furnace, a tubular furnace, a box furnace, a fluidized bed furnace, or the like can be used.

[0058] After completion of the chemical activation, it is preferable to provide a washing step in which the activated nitrogen-containing carbon material is washed with water to wash away metal components and the like used in the chemical activation, neutralized with hydrochloric acid, sulfuric acid, nitric acid, or the like, and washed again with water to wash away the acid.

[0059] After the washing step, the washed product is subjected to a solid-liquid separation treatment such as filtration, and then a drying treatment is performed.

[0060] After the chemical activation, the heat treatment may be performed in an inert gas, which may include, but is not limited to, nitrogen, argon, helium, neon, and other inert gases.

[0061] The inert gas atmosphere may be under reduced pressure, that is, a pressure environment lower than atmospheric pressure. Of these, it is preferable to use nitrogen gas as the inert gas. The inert gas atmosphere may be static or flowing, but is preferably flowing. The oxygen concentration in the inert gas is preferably 5% or less, more preferably 1% or less, and even more preferably 1000 ppm or less.

[0062] From the viewpoint of controlling the specific surface area and pore volume within the desired range, the lower limit of the heat treatment temperature is preferably 900° C. or higher, more preferably 1000° C. or higher, even more preferably 1100° C. or higher, even more preferably 1200° C. or higher, and even more preferably 1300° C. or higher. The upper limit of the temperature is preferably 1800° C. or lower, and more preferably 1600° C. or lower.

[0063] The heat treatment time is preferably from 10 seconds to 100 hours, more preferably from 5 minutes to 10 hours, even more preferably from 15 minutes to 5 hours, and even more preferably from 30 minutes to 2 hours.

[0064] When an inert gas is used, the pressure during the heat treatment is preferably 0.01 to 5 MPa, more preferably 0.05 to 1 MPa, even more preferably 0.08 to 0.3 MPa, and even more preferably 0.09 to 0.15 MPa.

[0065] The heat treatment can be carried out in the activation furnace described above.

[0066] The reduction rate of the nitrogen content defined by the following formula (I) in the activation step, for example, in the chemical activation step, is preferably 30 to 99% by mass.

[0067] Reduction rate of nitrogen content (mass%) = ((BA) / B) x 100 (I) (In formula (I), A is the nitrogen content (mass%) in the porous carbon material measured by XPS, and B is the nitrogen content (mass%) in the nitrogen-containing carbon material measured by XPS.)

[0068] The lower limit of the reduction rate of the nitrogen content is more preferably 75% by mass or more, and even more preferably 80% by mass or more. The upper limit is more preferably 98% by mass or less, and even more preferably 95% by mass or less. If the reduction rate of the nitrogen content is 30% by mass or more, micropores are developed, which is preferable. From the viewpoint of retaining nitrogen and from the viewpoint of setting the specific surface area and pore volume in the desired range, the reduction rate of the nitrogen content is preferably 99% by mass or less.

[0069] The reduction rate of the nitrogen content defined by the formula (I) can be controlled within the above numerical range by selecting the nitrogen-containing carbon material and the conditions in the activation step for the nitrogen-containing carbon material.

[0070] [Morphology of porous carbon materials] The porous carbon material used in the composite material of this embodiment is produced by a pulverization method. The pulverization may be carried out in any one of the production processes of the nitrogen-containing organic compound, the nitrogen-containing carbon material, and the porous carbon material.

[0071] The average particle size of the porous carbon material, as observed by SEM (scanning electron microscope), is preferably 0.1 to 100 μm, more preferably 0.5 to 20 μm, and even more preferably 1 to 5 μm. The aspect ratio is preferably 5 or less, more preferably 2 or less, and even more preferably 1.5 or less.

[0072] [Physical properties of porous carbon materials] The porous carbon material used in the composite material of this embodiment has a nitrogen content of 0.3 mass% or more and a specific surface area of ​​1000 m2 obtained by the BET method, which is a nitrogen adsorption / desorption method. 2 / g or more, and the pore volume obtained by quenched solid phase density function method (QSDFT) is 0.45 cm 3 / g or more.

[0073] The nitrogen content of the porous carbon material used in the composite material of this embodiment is measured by X-ray photoelectron spectroscopy (XPS) under the following conditions. [Measurement conditions]

[0074] X-ray source: Mg tube (Mg-Kα ray), tube voltage: 12kV, emission current: 50mA, analysis area: Φ600μm, capture area: N1s, C1s, O1s, Pass-Energy: 10eV

[0075] The lower limit of the nitrogen content in the porous carbon material used in the composite material of this embodiment is 0.3% by mass or more, preferably 0.5% by mass or more, more preferably 0.8% by mass or more, and even more preferably 1% by mass or more, from the viewpoint described later. Also, the upper limit of the nitrogen content is preferably 6% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less, from the viewpoint described later. The porous carbon material used in the composite material of the present embodiment can be formed by removing nitrogen atoms from a nitrogen-containing carbon material during an activation process of the nitrogen-containing carbon material, for example, a chemical activation process, leaving nitrogen atoms in a specific ratio. Nitrogen atoms have a superior affinity for sulfur atoms compared to carbon atoms due to the effect of their unpaired electrons. Therefore, it is considered that when the nitrogen content in the porous carbon material obtained after the activation step, for example the chemical activation step, is 0.3 mass% or more, sulfur can be effectively supported in the pores when a composite of the porous carbon material and sulfur is formed. In addition, when the nitrogen content is 6 mass % or less, it is believed that a porous carbon material having pores formed due to the loss of many nitrogen atoms can be obtained as described above, and therefore it is believed to be suitable as a positive electrode active material for lithium-sulfur batteries.

[0076] The oxygen content of the porous carbon material used in the composite material of this embodiment is preferably 2 to 20 mass %, more preferably 5 to 15 mass %, and further preferably 9 to 13 mass %.

[0077] The specific surface area of ​​the porous carbon material of this embodiment is 1000 m 2 / g or more, 1100m 2 / g or more is preferable, and 1300m 2 / g or more is more preferable, and 1500m 2 / g or more is more preferable. The specific surface area is 3000 m 2 / g or less is preferable, and 2500m 2 / g or less is more preferable.

[0078] The above range is preferable from the viewpoint of realizing a large discharge capacity per mass of sulfur and excellent cycle characteristics.

[0079] The specific surface area of ​​the porous carbon material can be controlled within the above-mentioned numerical range by adjusting the chemical activation conditions of the nitrogen-containing carbon material and the conditions of the heat treatment in an inert gas.

[0080] The pore volume obtained by the slit model of the quenched solid-state density functional method (QSDFT) for the nitrogen adsorption / desorption method is 0.45 cm 3 / g or more, and 3 / g or more is preferable, and 0.60 cm 3 / g or more is more preferable, and 0.70 cm3 / g or more is more preferable, and 0.80 cm 3 / g or more is even more preferable. The pore volume is 2.0 cm 3 / g or less is preferable, and 1.5 cm 3 / g or less is more preferable. In a lithium-sulfur battery using the composite material of the present embodiment containing a porous carbon material and sulfur as a positive electrode active material, the pore volume was 0.45 cm 3 / g or more, a porous carbon material can contain a large amount of sulfur, and therefore the discharge capacity per unit mass of the total of sulfur and carbon material is large, and therefore the discharge capacity per unit mass of the positive electrode is large.

[0081] The pore volume of the porous carbon material can be controlled within the above-mentioned numerical range by adjusting the activation conditions of the nitrogen-containing carbon material and the conditions of the heat treatment in an inert gas.

[0082] In addition, the porous carbon material used in the composite material of this embodiment has a pore volume of pores with diameters of 0.7 to 3 nm of 0.40 cm in a pore distribution diagram obtained by a slit model of the quenched solid-state density functional method (QSDFT) of the nitrogen adsorption / desorption method. 3 / g or more, and 0.60 cm 3 / g or more is more preferable, and 0.70 cm 3 It is more preferable that the molecular weight is 1 / g or more.

[0083] In addition, in the above pore distribution diagram, the pore volume of pores with diameters of 0.7 to 2 nm is 0.35 cm 3 / g or more, and 0.50 cm 3 / g or more is more preferable, and 0.60 cm 3 It is more preferable that the molecular weight is 1 / g or more.

[0084] FIG. 1 is an example of a laser Raman spectrum of a porous carbon material of this embodiment, and is an explanatory diagram of a method for calculating heights from the peaks (H1 and H2) and height from the minimum value M (L) from the spectrum.

[0085] The porous carbon material used in the composite material of this embodiment has a wavelength of 800 to 1900 cm as shown in the laser Raman spectrum of the porous carbon material shown in FIG. -1 In the laser Raman spectrum, 1250-1385 cm -1 Peak P1 between 1550 and 1620 cm -1 and the ratio (L / H1) of the height L from the baseline of the minimum point M between P1 and P2 to the height H1 of P1 from the baseline is preferably 0.40 to 0.65, from the viewpoint of achieving a larger discharge capacity per mass of sulfur and further improved cycle characteristics.

[0086] In this embodiment, the laser Raman spectrum is measured under the following conditions. [Measurement conditions] LD pumped solid-state laser λ: 532nm 47mW Measurement conditions 532nm irradiation 2.34mW Exposure time 10 seconds Accumulation 10 times Grating 600G / mm

[0087] In FIG. 1, P1 and P2 are the Raman shifts in the laser Raman spectrum of 1200 to 1700 cm -1 The two main peaks are between 1250 and 1385 cm. -1 P2 is a peak between 1550 and 1620 cm -1 It is the peak between.

[0088] The ratio (L / H1) is more preferably from 0.50 to 0.60, and further preferably from 0.55 to 0.58.

[0089] From the viewpoint of achieving a larger discharge capacity per sulfur mass and furthermore excellent cycle characteristics, the ratio (L / H2) is preferably 0.40 to 0.65, more preferably 0.50 to 0.60, and further preferably 0.55 to 0.59.

[0090] The ratio (H1 / H2) is preferably 0.5 to 2.0, and more preferably 0.7 to 1.3.

[0091] The half-width of peak P1 is 30 to 130 cm -1 is preferable, and 50 to 120 cm -1 More preferably, it is 100 to 110 cm -1 In this embodiment, the half width means the full width at half maximum (FWHM).

[0092] The half-width of peak P2 is 20 to 90 cm -1 is preferable, 40 to 80 cm -1 More preferably, 65 to 70 cm -1 It is.

[0093] It should be noted that FIG. 1 does not in any way limit the laser Raman spectrum obtained from the porous carbon material of this embodiment.

[0094] In Figure 1, B1 is 800-1250 cm -1 The minimum intensity value of B2 is 1700-1900 cm -1 is the minimum intensity value between The baseline in the laser Raman spectrum used in this embodiment is a straight line connecting B1 and B2.

[0095] Next, C1 and C2 shown in FIG. 1 are the intersecting points of the baseline and perpendicular lines drawn from peaks P1 and P2 to the Raman shift axis (horizontal axis), respectively.

[0096] D is the intersection point of the baseline and a perpendicular line drawn from the minimum intensity value M between the peaks P1 and P2 to the Raman shift axis (horizontal axis), and the height L is the length from the minimum intensity value M to the intersection point of the baseline and a perpendicular line drawn from the minimum intensity value M to the Raman shift axis. Specifically, the height L is the length of the line segment MD in the laser Raman spectrum illustrated in FIG.

[0097] On the other hand, the height H1 is the length from P1 to the intersection point of the perpendicular line from P1 to the Raman shift axis and the baseline. Specifically, in the laser Raman spectrum illustrated in FIG. 1, the length of the line segment P1C1 corresponds to the height H1.

[0098] The height H2 is the length from P2 to the intersection of the perpendicular line from P2 to the Raman shift axis and the baseline. Specifically, in the laser Raman spectrum illustrated in FIG. 1, the length of the line segment P2C2 corresponds to the height H2.

[0099] (sulfur) The composite material of the present embodiment contains sulfur. The sulfur is not particularly limited as long as it is an element or compound containing sulfur. Examples of such sulfur include elemental sulfur (S) and compound lithium sulfide (Li2S). Elemental sulfur (S) is preferred. In this embodiment, elemental sulfur (S) is referred to as sulfur.

[0100] (Method of manufacturing composite material containing porous carbon material and sulfur) The method for producing a composite material containing a porous carbon material and sulfur according to the present embodiment includes a step of mixing the porous carbon material and sulfur. In the process for producing the composite material of this embodiment, other additives may be contained within a range that does not impair the effects of this embodiment.

[0101] The mixing method will be described. Examples of the mixing method include a method of mixing the porous carbon material and sulfur in a dry atmosphere, and a method of mixing the porous carbon material and sulfur in a wet atmosphere in the presence of a solvent and then removing the solvent. An example of a method for mixing the porous carbon material and sulfur in a dry or wet atmosphere is to place the porous carbon material and sulfur in a mixer, and mix them in the mixer. Examples of the mixer include a mortar and a ball mill.

[0102] The method for producing the composite material includes a step of melting sulfur and filling the porous carbon material with the melted sulfur.

[0103] After the step of mixing the porous carbon material with sulfur, the sulfur is melted by heating to a temperature equal to or higher than the melting point of sulfur, and the sulfur is impregnated and filled into the pores of the porous carbon material by capillary action.

[0104] The heating temperature may be equal to or higher than 107° C., which is the melting point of sulfur, but is preferably equal to or higher than 130° C., and more preferably equal to or higher than 150° C. The heating temperature is preferably equal to or lower than 200° C., more preferably equal to or lower than 180° C., and even more preferably equal to or lower than 170° C.

[0105] From the viewpoint of suppressing the volatilization of sulfur, the impregnation of the pores with sulfur is preferably carried out in a closed vessel. The reaction time is preferably 0.1 to 100 hours, more preferably 0.5 to 20 hours, and further preferably 1 to 10 hours.

[0106] The atmosphere may be air or an inert gas such as nitrogen, argon, helium, or neon.

[0107] Next, in order to remove the sulfur that has not been filled into the pores, the porous carbon material that has been impregnated with sulfur is heated. The heating temperature is preferably 250° C. or higher, more preferably 270° C. or higher, and even more preferably 290° C. or higher. The heating temperature is preferably 500° C. or lower, preferably 400° C. or lower, and even more preferably 330° C. or lower.

[0108] The heating time is preferably 0.5 hours or more, more preferably 1 hour or more, and even more preferably 2 hours or more.

[0109] The container may be a sealed container or an open container. In the case of a sealed container, it is preferable that the temperature of the upper part of the container is lower than that of the heating part. The atmosphere may be air or an inert gas such as nitrogen, argon, helium, or neon, but air is preferable from the viewpoint of ease of operation.

[0110] The mass ratio when mixing the composite material and sulfur is preferably 0.3 parts by mass or more, more preferably 0.9 parts by mass or more, and even more preferably 1.1 parts by mass or more, per 1 part by mass of the porous carbon material, from the viewpoint of filling the pores of the porous carbon material with sulfur sufficiently. The mass ratio is such that the sulfur that is not filled in the pores of the porous carbon material and remains on the surface is evaporated and removed, and from the viewpoint of reducing the amount of evaporated material and reducing the energy required for evaporation, the mass ratio is preferably 20 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 5 parts by mass or less, per 1 part by mass of the porous carbon material.

[0111] The sulfur content in the composite material of this embodiment is preferably 35 to 90 mass%. From the viewpoint of further increasing the discharge capacity per composite material, the lower limit of the sulfur content is preferably 40 mass% or more, more preferably 43 mass% or more, and even more preferably 45 mass% or more. From the viewpoint of production of the porous carbon material, the upper limit of the sulfur content is 70 mass% or less, more preferably 67 mass% or less, and even more preferably 65 mass% or less.

[0112] The content of the porous carbon material in the composite material of this embodiment is preferably 10 to 65 mass%. The lower limit of the content of the porous carbon material is preferably 30 mass% or more, more preferably 33 mass% or more, and even more preferably 35 mass% or more. The upper limit of the content of the porous carbon material is 60 mass% or less, more preferably 57 mass% or less, and even more preferably 55 mass% or less.

[0113] In this embodiment, the sulfur content (mass%) is calculated by the following formula: Sulfur content = (mass of sulfur) / (mass of porous carbon material and composite material containing sulfur) x 100 This is the value calculated by:

[0114] The sulfur content in the composite material of this embodiment can be measured by thermogravimetric analysis (TG) by preparing a sample in the following manner, taking advantage of the fact that sulfur trapped in the micropores of a porous carbon material is difficult to evaporate, whereas sulfur outside the micropores is easy to evaporate.

[0115] After mixing the porous carbon material and sulfur, the mixture is kept in a sealed container at 155°C for 5 hours to melt the sulfur and fill the pores of the porous carbon material by capillary action.The mixture is then heated to 300°C and kept for 2 hours to evaporate and remove the sulfur remaining on the surface of the porous carbon material.The mixture is then air-cooled to room temperature, the container is opened, and the composite material containing the porous carbon material and sulfur is taken out to prepare a sample.

[0116] Next, the sulfur content in the composite material containing the porous carbon material and sulfur is measured by thermogravimetric analysis (TG). Specifically, a Shimadzu DTG-60AH is used, 10 mg of the sample is placed in the cell, and the measurement is performed under the following conditions: measurement gas: Ar, flow rate: 50 ml / min., starting temperature: 30°C, heating rate: 5°C / min., and upper limit temperature: 600°C.

[0117] For convenience, the method for calculating the sulfur content will be described with reference to FIG. 2 which is a graph of thermogravimetric analysis (TG) obtained by measuring the composite material containing porous carbon material and sulfur produced in the below-mentioned Example [Composite material containing porous carbon material and sulfur] under the above-mentioned conditions.

[0118] In the thermogravimetric analysis (TG) graph shown in Figure 2, the mass decreases as the temperature increases, which corresponds to the sublimation of the sulfur filled in the pores. In the region between 300°C and 500°C, a point appears where the slope of the tangent line to the graph changes discontinuously. This corresponds to the fact that only the porous carbon material remains at this point.

[0119] If the initial mass % is 100 and the mass % at the point where the slope of the tangent line to the graph changes discontinuously is X, the sulfur content Y of the composite material is the initial value (100) minus the proportion of the porous carbon material X, and is therefore defined as "Y = 100 - X".

[0120] For reference, when only sulfur is subjected to TG measurement using this measurement method, it is found that sulfur sublimes by 300°C and no sulfur remains, as shown in Figure 2. X = 0, Y = 100, and the sulfur content Y is calculated to be 100 mass%.

[0121] The composite material containing the porous carbon material and sulfur of this embodiment preferably has substantially no peaks characteristic of sulfur in an X-ray diffraction diagram (XRD) obtained using CuKα radiation as an X-ray source.

[0122] The characteristic peaks of sulfur include a strong peak P2 at 23.0°±0.3°, and other peaks at 15.3°±0.3°, 25.8°±0.3°, 26.7°±0.3°, and 27.7°±0.3°.

[0123] The porous carbon material has a broad peak P1 at 23.2 to 24.5° in XRD. In this embodiment, "substantially free of peaks characteristic of sulfur" means that when the intensity of peak P2 is I(P2) and the intensity of peak P1 is I(P1), I(P2) / I(P1) is 0.2 or less, preferably 0.1 or less, and more preferably 0.05 or less.

[0124] (Lithium-sulfur battery cathode) The positive electrode of the lithium-sulfur battery of this embodiment contains the composite material containing the porous carbon material obtained as described above and sulfur. The positive electrode of the lithium-sulfur battery of this embodiment includes the composite material of this embodiment, and, as necessary, a binder, a conductive assistant, and a current collector. The composite material functions as an active material, but the positive electrode of the lithium-sulfur battery of this embodiment may contain an active material other than the composite material containing the porous carbon material and sulfur.

[0125] The binder used in the positive electrode of the present embodiment is not particularly limited, and examples thereof include polyvinylidene fluoride, polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinyl fluoride, vinylidene fluoride-hexafluoropropylene-based fluororubber, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene-based fluororubber, vinylidene fluoride-pentafluoropropylene-based fluororubber, and vinylidene fluoride. Examples of the fluororubbers include vinylidene fluoride-based fluororubbers such as vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene-based fluororubbers, vinylidene fluoride-perfluoromethylvinyl ether-tetrafluoroethylene-based fluororubbers, and vinylidene fluoride-chlorotrifluoroethylene-based fluororubbers, tetrafluoroethylene-propylene-based fluororubbers, tetrafluoroethylene-perfluoroalkylvinyl ether-based fluororubbers, thermoplastic fluororubbers, polyethylene, polypropylene, styrene butadiene rubber (SBR), isoprene rubber, butadiene rubber, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, aqueous binders, and polyacrylonitrile. These may be used alone or in any combination and ratio of two or more.

[0126] The content of the binder is preferably 1 to 20% by mass, and more preferably 2 to 10% by mass, relative to 100% by mass of the active material. When the content of the binder is 1% by mass or more, the strength of the positive electrode becomes sufficient, and when the content of the binder is 20% by mass or less, the increase in electrical resistance or the decrease in capacity can be further suppressed.

[0127] The conductive assistant used in the positive electrode of the present embodiment is not particularly limited, but may be, for example, carbon black, acetylene black, or carbon nanotubes. These may be used alone or in any combination and ratio of two or more.

[0128] The content of the conductive assistant is preferably 1 to 20 mass %, and more preferably 2 to 15 mass %, relative to 100 mass % of the active material.

[0129] The current collector used in the positive electrode of this embodiment is not particularly limited as long as it allows electrical connection of the electrode, and examples of the material include aluminum, titanium, zirconium, hafnium, niobium, tantalum, and alloys containing these metals. Among these, those selected from the group consisting of aluminum, titanium, tantalum, and alloys containing these metals are preferred, and aluminum is more preferred. These metals or alloys can be made into a foil, a perforated foil, a mesh, or the like, and used as the current collector for the positive electrode.

[0130] Next, a method for producing the positive electrode of the lithium-sulfur battery of this embodiment will be described. The method for producing the positive electrode of the lithium-sulfur battery of the present embodiment is not particularly limited as long as it is a known method, except that the composite material of the present embodiment containing a porous carbon material and sulfur is used as the active material.

[0131] For example, a method can be used in which a positive electrode for a lithium-sulfur battery is produced by adding a binder, a conductive assistant, and a solvent to a composite material containing a porous carbon material and sulfur to form a slurry, applying or filling the slurry onto a current collector, drying the current collector, and then pressing the current collector to increase density.

[0132] The thickness of the positive electrode layer laminated on the current collector is preferably about 20 to 400 μm. If the thickness of the positive electrode layer is 20 μm or more, the ratio of the amount of active material to the entire battery increases, and the energy density tends to increase, which is preferable. On the other hand, if the thickness of the positive electrode layer is 400 μm or less, the resistance inside the electrode decreases, and the output density tends to increase, which is preferable.

[0133] The solvent used in the manufacture of the positive electrode of the lithium-sulfur battery of this embodiment may be either aqueous or non-aqueous. The non-aqueous solvent is not particularly limited, but examples thereof include N-methylpyrrolidone, methyl ethyl ketone, cyclohexanone, isophorone, N,N-dimethylformamide, and N,N-dimethyl.

[0134] The above-mentioned slurry is prepared by kneading using a dispersing device such as a stirrer, a pressure kneader, a ball mill, or a super sand mill.

[0135] In addition, a thickener may be added to the above-mentioned slurry to adjust the viscosity. The thickener is not particularly limited, but examples thereof include carboxymethylcellulose (CMC), methylcellulose, hydroxymethylcellulose, ethylcellulose, polyvinyl alcohol, polyacrylic acid (salt), oxidized starch, phosphorylated starch, and casein. These may be used alone or in any combination and ratio of two or more.

[0136] <Negative electrode> The negative electrode active material used in the negative electrode may be any material containing lithium, such as metallic lithium, lithium alloys, lithium oxides, lithium composite oxides, lithium sulfides, lithium composite sulfides, and carbon materials pre-doped with lithium. Examples of the lithium alloy include alloys of lithium with aluminum or silicon, tin, magnesium, indium, and calcium. The negative electrode active material is preferably metallic lithium or an alloy of silicon and lithium. Examples of the lithium composite oxide include lithium titanate. Examples of the carbon material pre-doped with lithium include graphite, hard carbon, soft carbon, carbon black, acetylene black, activated carbon, carbon fiber, and coke. The negative electrode can be manufactured by forming a negative electrode layer containing a negative electrode active material on a current collector in the same manner as the positive electrode.

[0137] The negative electrode may be formed by mixing a negative electrode active material with a conductive assistant such as graphite, acetylene black, or ketjen black, and a binder, adding an appropriate solvent to form a paste-like negative electrode material, applying it to the surface of a current collector, drying it, and compressing it to increase the electrode density as necessary. The negative electrode current collector is not particularly limited as long as it allows electrical connection of the electrode, and its material is not particularly limited, but examples thereof include copper, aluminum, nickel, titanium, and stainless steel. Of these, copper is preferred from the viewpoint of ease of processing into a thin film and from the viewpoint of cost. Examples of the shape of the current collector include foil, perforated foil, and mesh. In addition, porous materials such as porous metal (foamed metal) and carbon paper can also be used as the current collector.

[0138] <Electrolyte> The electrolytic solution contains a first solvent having a sulfonyl group, a second solvent which is a fluorine-based solvent, and a lithium-containing electrolyte. The sulfonyl group is -S(=O2)-. Examples of the first solvent having a sulfonyl group include sulfolane (SL), 3-methylsulfolane, ethyl methyl sulfone, and ethyl isopropyl sulfone. These may be used alone or in combination of two or more. Among them, sulfolane and ethyl methyl sulfone are preferred, and sulfolane is more preferred. Examples of lithium-containing electrolytes include LiPF6, LiClO4, LiBF4, LiAsF6, LiCF(CF3)5, LiCF2(CF3)4, LiCF3(CF3)3, LiCF4(CF3)2, LiCF5(CF3), LiCF3(C2F5)3, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(C2F5CO)2, LiI, LiAlCl4, LiBC4O8, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(fluorosulfonyl)imide (LiFSI).

[0139] These may be used alone or in combination of two or more. Among these, LiPF6, LiFSI, and LiTFSI are preferred, and LiTFSI is more preferred.

[0140] The ratio of the lithium-containing electrolyte to the first solvent having a sulfonyl group in the electrolytic solution is 1.0 to 8.0 mol, preferably 2.1 to 6.0 mol, more preferably 2.3 to 5.5 mol, and even more preferably 2.5 to 4.0 mol, of the first solvent having a sulfonyl group per mol of lithium in the lithium-containing electrolyte. At a high concentration of less than 1.0 mol, the first coulombic efficiency is low, and at a low concentration of more than 8.0 mol, the cycle characteristics are poor. The reason is unclear, but it is thought that when the lithium-containing electrolyte in the electrolyte solution becomes highly concentrated, a bridge structure is formed by coordination bonding with the oxygen of the sulfonyl group of the adjacent solvent molecule through the lithium ion, and the lithium ion hops to the site where the adjacent lithium ion is coordinated. If the concentration is less than 1.0 mol, the reaction from Li2S to S8 does not proceed sufficiently, and if the concentration is low and exceeds 8.0 mol, polysulfide elution occurs.

[0141] The electrolyte contains a fluorine-based solvent as a second solvent. As the fluorine-based solvent, fluoroethylene carbonate (FEC), 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)-propane (HFE), and mixtures thereof are preferred. HFE is more preferred.

[0142] The ratio of the second solvent is preferably 0.1 to 5 mol, more preferably 0.25 to 3 mol, and further preferably 0.2 to 1.5 mol, relative to 1 mol of the first solvent. The second solvent is preferably 0.1 mol or more from the viewpoint of decreasing the viscosity and improving the ionic conductivity, and is preferably 5 mol or less from the viewpoint of promoting the hopping effect of lithium ions by the sulfonyl group.

[0143] <separator> The separator is not particularly limited in material or shape as long as it is one that is used in ordinary lithium-sulfur batteries. This separator separates the positive electrode and the negative electrode so that they do not come into physical contact with each other, and it is preferable that the separator has high ion permeability.

[0144] Examples of the separator include a synthetic resin microporous membrane, a woven fabric, and a nonwoven fabric, and the synthetic resin microporous membrane is preferred. Examples of the material of the synthetic resin microporous membrane include polyolefins such as polyethylene, polypropylene, and polybutene; polyamide, cellulose acetate, nitrocellulose, polysulfone, polyacrylonitrile, and polyvinylidene fluoride.

[0145] Among these, polyethylene and polypropylene are preferable. When the lithium-sulfur battery to be produced is structured so that the positive electrode and the negative electrode are not in direct contact with each other, it is not necessary to use a separator.

[0146] The structure of the electrode body of the lithium-sulfur battery of this embodiment is not particularly limited, but typically, the positive electrode and negative electrode, and a separator that is provided as necessary, are wound into a flat spiral shape to form a wound electrode plate group, or these are stacked in the form of flat plates to form a stacked electrode plate group, and the electrode plate group is then enclosed in an exterior body.

[0147] <Exterior body> The exterior body may be a metal can, a laminate film, or the like. The metal can is preferably made of aluminum. In this case, for example, the metal can serves as a negative electrode terminal, and a metal lid crimped to the metal can with an insulator sandwiched therebetween serves as a positive electrode terminal. The electrode body and the terminal are electrically connected by an electrode tab.

[0148] The laminate film is preferably a film in which a metal foil and a resin film are laminated, and an example of the laminate film is a three-layer structure consisting of an outer layer resin film / metal foil / inner layer resin film. The outer layer resin film is for preventing the metal foil from being damaged by contact, etc., and resins such as nylon or polyester can be suitably used.

[0149] The metal foil is for preventing the permeation of moisture and gas, and foils of copper, aluminum, stainless steel, etc. can be suitably used. The inner layer resin film is for protecting the metal foil from the electrolyte contained inside and for melt sealing during heat sealing, and polyolefin, acid-modified polyolefin, etc. can be suitably used.

[0150] When a laminate film exterior body is used, the edges of the laminate film are sealed with the ends of the electrode terminals extended into the external space of the exterior body, preferably by heat sealing.

[0151] The lithium-sulfur battery of this embodiment can be in the form of a paper type battery, a button type battery, a coin type battery, a laminated type battery, a cylindrical type battery, or the like.

[0152] <Operation of lithium-sulfur batteries> The lower limit of the cut-off voltage in the lithium-sulfur battery is preferably 0.8 V, more preferably 1.0 V, even more preferably 1.2 V, and even more preferably 1.4 V, in order to suppress side reactions other than the charge and discharge reactions. The upper limit of the cut-off voltage in the lithium-sulfur battery is preferably 4.0 V, more preferably 3.7 V, even more preferably 3.4 V, and even more preferably 3.0 V. In this embodiment, the cut-off voltage refers to a reference voltage for determining the end of charge or discharge of a lithium-ion battery.

[0153] The lithium-sulfur battery of the present embodiment has an electrode assembly including a negative electrode and a positive electrode arranged opposite each other with a separator interposed therebetween, and an exterior body that houses the electrode assembly, and can be manufactured by injecting an electrolyte into the space within the exterior body and sealing it. EXAMPLES

[0154] Hereinafter, the present embodiment will be described in more detail with reference to specific examples and comparative examples. However, these are merely illustrative, and the present embodiment is not limited in any way by the following examples and comparative examples. Therefore, those skilled in the art can carry out the present invention by making various modifications to the examples shown below, and such modifications are encompassed by the present invention.

[0155] [Analysis method] (CHN analysis method) The nitrogen-containing carbon material was used as the measurement sample. Using an elemental analyzer manufactured by J Science Labs (product name "MICRO CORDER JM10"), 2500μg of sample was loaded onto the sample stage and CHN analysis was performed. The temperature of the sample furnace was set to 950℃, the temperature of the combustion furnace (copper oxide catalyst) to 850℃, and the temperature of the reduction furnace (consisting of a silver grain + copper oxide zone, a reduced copper zone, and a copper oxide zone) to 550℃. The oxygen flow rate was set to 15mL / min, and the He flow rate to 150mL / min. A thermal conductivity detector (TCD) was used as the detector. Calibration was performed using antipyrine according to the method described in the manual. The content (mass%) of oxygen element was calculated by subtracting the contents (mass%) of carbon element, nitrogen element, and hydrogen element from 100 mass%.

[0156] (Specific surface area, pore distribution diagram, and pore volume) The porous carbon material was used as a measurement sample. The specific surface area was measured by the BET method using Quantachrome's AUTOSORB iQ. In addition, a pore distribution diagram was obtained using the slit model of the quenched solid-phase density function method (QSDFT) of the nitrogen adsorption / desorption method, and the pore volume was calculated using the diagram. Specifically, the sample was degassed under vacuum for 3 hours at 100° C. and then the measurement was performed. The nitrogen adsorption isotherm was measured at liquid nitrogen temperature, and the specific surface area, pore distribution, and pore volume were measured.

[0157] (X-ray photoelectron spectroscopy (XPS) measurement method) The nitrogen-containing carbon material and the porous carbon material were used as measurement samples. Using JPS-9010MC (product name) manufactured by JEOL, the powder cell was filled with the measurement sample and measured under the following conditions. (conditions) X-ray source: Mg tube (Mg-Kα ray), tube voltage: 12kV, emission current: 50mA, analysis area: Φ600μm, capture area: N1s, C1s, O1s, Pass-Energy: 10eV The obtained spectrum was energy-corrected at the C1s peak position. The total content (mass%) of carbon, nitrogen, and oxygen elements was set to 100 mass%.

[0158] (Method of measuring laser Raman spectrum) The porous carbon material was used as a measurement sample. Using a 3D microscopic laser Raman spectrometer Nanofinder30 (product name) manufactured by Tokyo Instruments Inc., the measurement sample was filled into a powder cell and measured under the following conditions. (conditions) LD-pumped solid-state laser λ:532nm 47mW Measurement conditions 532nm, irradiation 2.34mW, exposure time 10 seconds, cumulative 10 times, grating 600G / mm 1250~1385cm -1 The peak between these is designated as P1. 1550~1620cm -1 The peak between these is designated as P2. Let L be the height from the baseline of the minimum point M between P1 and P2. The height of P1 from the baseline is H1. The height of P2 from the baseline is H2.

[0159] (SEM measurement method) Porous carbon materials and composite materials were measured. A scanning microscope (SU-1500 (product name), Hitachi High-Tech Solutions, manufactured by Hitachi High-Technologies Corporation) was used. Each powder sample was attached to an aluminum sample stage using conductive carbon tape, and the stage was then installed inside the chamber. After the chamber was evacuated, the sample was observed at a working distance of 15 mm and an accelerating voltage of 15 kV. The average particle size and aspect ratio of the porous carbon material were measured.

[0160] (Method of measuring sulfur content) The sulfur content of the porous carbon material and the sulfur-containing composite material was measured by thermogravimetric analysis (TG) as follows. Using a Shimadzu DTG-60AH, 10 mg of sample was placed in the cell and measurements were performed under the following conditions: measurement gas: Ar, flow rate: 50 mL / min, starting temperature: 30°C, heating rate: 5°C / min, and upper limit temperature: 600°C. The method for calculating the sulfur content from the obtained thermogravimetric analysis (TG) will be explained with reference to FIG. In the thermogravimetric (TG) graph, the mass decreases as the temperature increases, which corresponds to the sublimation of the sulfur filled in the pores. In the region between 300°C and 500°C, a point appears where the slope of the tangent line to the graph changes discontinuously. This corresponds to the fact that only the porous carbon material remains at this point. If the initial mass % is 100 and the mass % at the point where the slope of the tangent line to the graph changes discontinuously is the porous carbon material content X, the sulfur content Y is the value obtained by subtracting the proportion of the porous carbon material from the initial value (100), and is therefore defined as Y=100-X.

[0161] [Example of production of nitrogen-containing carbon material] [Production of azulmic acid] An aqueous solution of 150 g of hydrocyanic acid was prepared in a vessel by dissolving it in 350 g of water, and while stirring this aqueous solution, 120 g of 25% aqueous ammonia solution was added over 10 minutes, and the resulting mixture was heated to 35°C. Then, polymerization of hydrocyanic acid started, and a black-brown polymer started to precipitate, and the temperature gradually rose to 45°C. Two hours after the initiation of polymerization, a 30% by mass aqueous solution of hydrocyanic acid was started to be added at a rate of 200 g / hour, and 800 g was added over 4 hours. During the addition of the aqueous hydrogen cyanide solution, the vessel was cooled to control the reaction temperature to be maintained at 50° C. The polymerization reaction solution was stirred at this temperature for 100 hours. The black precipitate obtained was separated by filtration. The yield of the precipitate was 96% by mass based on the total amount of hydrocyanic acid used. The separated precipitate was washed with water and then dried in a dryer at 120° C. for 4 hours to obtain azulmic acid.

[0162] The obtained azulmic acid was subjected to CHN analysis using an elemental analyzer manufactured by J Science Labs (product name "MICRO CORDER JM10") by loading 2500 μg of the azulmic acid sample onto the sample stage. The temperature of the sample furnace was set to 950°C, the temperature of the combustion furnace (copper oxide catalyst) to 850°C, and the temperature of the reduction furnace (consisting of a silver grain + copper oxide zone, a reduced copper zone, and a copper oxide zone) to 550°C. The oxygen flow rate was set to 15 mL / min, and the He flow rate to 150 mL / min. A thermal conductivity detector (TCD) was used as the detector. Calibration was performed using antipyrine according to the method described in the manual. As a result, the composition of the azulmic acid obtained as described above was 40.0% by mass of carbon element, 29.8% by mass of nitrogen element, and 4.1% by mass of hydrogen element. Here, since adsorbed water remains under the above-mentioned drying conditions, it is considered that the difference is mainly due to oxygen and hydrogen elements in the adsorbed water.

[0163] [Production of nitrogen-containing carbon material] 6.7 g of azulmic acid obtained as described above was filled into a quartz tube with an inner diameter of 25 mm, and the temperature was raised to 800 °C over 1 hour and 20 minutes in a nitrogen gas stream of 550 Ncc / min. under atmospheric pressure, held at 800 °C for 1 hour for carbonization treatment, and then pulverized with a planetary ball mill to obtain a nitrogen-containing carbon material. <CHN analysis method> The CHN analysis results (atomic ratio, mass%) of the nitrogen-containing carbon material are shown in Table 1 below. <XPS analysis method> The XPS analysis results (atomic ratio, mass%) of the nitrogen-containing carbon material are shown in Table 1 below.

[0164]

Table 1

[0165] 〔Production of porous carbon material〕 2 g of the nitrogen-containing carbon material obtained in the above-mentioned 〔Production of nitrogen-containing carbon material〕 was added to a mixed solution of 4 g of potassium hydroxide and 20 mL of pure water, and water was removed at 100 °C while stirring to prevent precipitation. Thereafter, the sample was transferred to a quartz boat, placed in the quartz tube of a horizontal tubular furnace, argon gas was flowed at a flow rate of 500 Ncc / min., and gas exchange was performed by leaving it for 5 minutes. After the exchange, the temperature was raised to 150 °C over 15 minutes, and the content was dried by heat treatment at 150 °C for 1 hour. Thereafter, the temperature was raised to 800 °C over 1 hour, heat treatment was performed for 1 hour, and then the temperature was lowered to recover the content. The content was washed with 0.3 L of water, further washed with 0.5 L of 1 mol / L hydrochloric acid aqueous solution, then washed with water until the furnace liquid became almost neutral, recovered by filtration, and dried to obtain a porous carbon material. This operation was repeated to mass-produce the porous carbon material. The average particle diameter was observed by SEM to be about 5 to 10 μm, and the aspect ratio was generally 1.5 or less.

[0166] <XPS analysis> The XPS analysis results (atomic ratio, mass%) of the porous carbon material are shown in Table 2 below. The reduction rate of the nitrogen content was 85 mass% (=((14.59-2.19) / 14.59)×100). <Raman analysis> The laser Raman spectrum of the porous carbon material is shown in FIG. 3, and the results calculated from the spectrum are shown in Table 2. <Measurement of specific surface area and pore volume> The specific surface area of ​​the porous carbon material is shown in Table 2. The pore distribution diagram of the porous carbon material is shown in FIG. 4, and the results calculated from FIG. 4 are shown in Table 2.

[0167] [Table 2]

[0168] [Production of composite material containing porous carbon material and sulfur] Sulfur was added to 0.43 g of the porous carbon material produced as described above so that the ratio of the porous carbon material to the sulfur was 40:60 (mass ratio), and the mixture was mixed in a mortar for 10 minutes. The mixture was then placed in a closed container with an inner diameter of 20 mm and a height of 60 mm, and held at 155°C for 5 hours to melt the sulfur, which was then filled into the pores of the porous carbon material by capillary action. The temperature was then raised to 300°C and held for 2 hours to evaporate and remove the residual sulfur. The container was air-cooled to room temperature and then opened to obtain a composite material containing a porous carbon material and sulfur. The entire composite process was carried out under air.

[0169] <Measurement of sulfur content> The sulfur contents of the obtained porous carbon material and the composite material containing sulfur were measured by thermogravimetric analysis (TG). As a result, as shown in Figure 2, the porous carbon material content (X) was 42, the sulfur content (Y) was 58, and the sulfur content Y was 58 mass% (Table 3).

[0170] [Table 3]

[0171] [Preparation of lithium-sulfur battery] (Making positive electrodes for lithium-sulfur batteries) Carboxymethyl cellulose (CMC) (thickener) was dissolved in pure water to prepare a 2% by mass solution. Acetylene black (conductive additive) was added thereto, and then active materials (composite materials containing porous carbon materials and sulfur produced in Examples 1 and 2 described below, and composites of porous carbon materials and sulfur produced in Comparative Examples 1 and 2) and styrene-butadiene rubber (SBR) (binder) were added thereto to prepare a positive electrode slurry. The mass ratio of the active material, conductive assistant, thickener, and binder was set to be active material:conductive assistant:thickener:binder=84:10:3:3. The obtained positive electrode slurry was applied to an aluminum (Al) current collector foil (current collector) in an amount of about 2.0 mg / cm2 as active material. 2 The mixture was filled so that the volume was 1000 g. Then, it was dried in an oven at 40°C under atmospheric pressure for 1 hour. After drying, the dried product was passed through a roll press to be pressure-molded, punched out to a size of Φ12 mm with a punch, and dried in an oven at 50°C under vacuum to obtain a positive electrode for a lithium-sulfur battery. The thickness of the positive electrode layer was about 75 μm.

[0172] (Preparation of anodes for lithium-sulfur batteries) In an air atmosphere with a dew point of -40°C or less, a 200 μm thick Li (lithium) foil was punched out with a Φ13 mm punch to prepare a negative electrode for a lithium-sulfur battery.

[0173] (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated in an air atmosphere with a dew point of -40°C or lower by the following procedure. The positive electrode prepared according to the above item (Preparation of a positive electrode for a lithium-sulfur battery), the negative electrode prepared according to the above item (Preparation of a negative electrode for a lithium-sulfur battery), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as a lithium-containing electrolyte, sulfolane (SL) as a first solvent having a sulfonyl group, and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)-propane (HFE) as a second solvent, which is a fluorine-based solvent, were used. As the separator, a polypropylene-based microporous film was used. A two-electrode flat cell was used as the cell, and a positive electrode, a separator, and a negative electrode were stacked in this cell in this order, and an electrolyte was further injected to prepare a lithium-sulfur battery.

[0174] [Charge / discharge test] The active material (positive electrode) was used as a working electrode, and a constant current charge / discharge test was carried out. The charging mode was the CC method (CC is an abbreviation for constant current), and the discharging mode was the CC mode. The set current density was 167.2 mA / g (a current density of 1672 mA / g is defined as 1 C. Hereinafter, 167.2 mA / g will be indicated as 0.1 C). Regarding the cutoff voltage, the lower limit was set to 1.0 V and the upper limit was set to 3.0 V in Examples 1 to 7 and Comparative Examples 1 and 2. In Example 8, the lower limit was set to 1.5 V and the upper limit was set to 3.0 V. In Example 9, the lower limit was set to 1.5 V and the upper limit was set to 3.5 V. All charge and discharge tests were carried out in an environment of 25°C. The charge capacity and discharge capacity were defined per mass of sulfur. The coulombic efficiency was calculated by the following formula. Coulombic efficiency (%) = ((Charge capacity (mAh / g-sulfur)) / (Discharge capacity (mAh / g-sulfur))) x 100

[0175] [Cyclic voltammetry (CV) measurement] The measurements were performed at a scan rate of 0.05 mV / s, a voltage range of 1.0 V to 3.0 V, and a temperature of 25° C. The numbers in the figure indicate the cycle numbers.

[0176] Comparative Example 1 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated according to the method for fabricating a lithium-sulfur battery. The amounts (mol) of LiTFSI, SL, and HFE, as well as the molar ratios, are shown in Table 4. (Charge / discharge test) A charge-discharge test was carried out at 0.1C. The results are shown in Table 4. The first charge-discharge curve is shown in Figure 5. The cycle characteristics are shown in Figure 6. The CV is shown in Figure 10.

[0177] Example 1 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated according to the method for fabricating a lithium-sulfur battery. The amounts (mol) of LiTFSI, SL, and HFE, as well as the molar ratios, are shown in Table 4. (Charge / discharge test) A charge-discharge test was carried out at 0.1C. The results are shown in Table 4. The first charge-discharge curve is shown in Figure 5. The cycle characteristics are shown in Figure 6. The CV is shown in Figure 11.

[0178] Example 2 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated according to the method for fabricating a lithium-sulfur battery. The amounts (mol) of LiTFSI, SL, and HFE, as well as the molar ratios, are shown in Table 4. (Charge / discharge test) A charge-discharge test was carried out at 0.1C. The results are shown in Table 4. The first charge-discharge curve is shown in Figure 5. The cycle characteristics are shown in Figure 6. The CV is shown in Figure 12.

[0179] Example 3 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated according to the method for fabricating a lithium-sulfur battery. The amounts (mol) of LiTFSI, SL, and HFE, as well as the molar ratios, are shown in Table 4. (Charge / discharge test) The charge-discharge test was carried out at 0.1C with a cut-off voltage lower limit of 1.0V and an upper limit of 3.0V. The results are shown in Table 4. The first charge-discharge curve is shown in Figure 5. The first, second and 30th charge-discharge characteristics are shown in Figure 8. The cycle characteristics are shown in Figures 6, 7 and 9. The CV is shown in Figure 13.

[0180] Example 4 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated according to the method for fabricating a lithium-sulfur battery. The amounts (mol) of LiTFSI, SL, and HFE, as well as the molar ratios, are shown in Table 4. (Charge / discharge test) A charge-discharge test was carried out at 0.1C. The results are shown in Table 4. The first charge-discharge curve is shown in Figure 5. The cycle characteristics are shown in Figure 6. The CV is shown in Figure 14.

[0181] Example 5 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated according to the method for fabricating a lithium-sulfur battery. The amounts (mol) of LiTFSI, SL, and HFE, as well as the molar ratios, are shown in Table 4. (Charge / discharge test) A charge-discharge test was carried out at 0.1 C. The results are shown in Table 4. The first charge-discharge curve is shown in Figure 5. The CV is shown in Figure 15.

[0182] Example 6 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated according to the method for fabricating a lithium-sulfur battery. The amounts (mol) of LiTFSI, SL, and HFE, as well as the molar ratios, are shown in Table 4. (Charge / discharge test) A charge / discharge test was carried out at 0.1 C. The results are shown in Table 4. The cycle characteristics are shown in Figure 7.

[0183] Example 7 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated according to the method for fabricating a lithium-sulfur battery. The amounts (mol) of LiTFSI, SL, and HFE, as well as the molar ratios, are shown in Table 4. (Charge / discharge test) A charge / discharge test was carried out at 0.1 C. The results are shown in Table 4. The cycle characteristics are shown in Figure 7.

[0184] Comparative Example 2 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated by repeating Comparative Example 1, except that tetraglyme (G4) was used as the first solvent instead of sulfolane (SL), and the molar ratio of LiTFSI, G4, and HFE was LiTFSI:G4:HFE=10:8:40. This electrolyte composition is a suitable composition ratio when G4 is used. The amounts (mol) of LiTFSI, G4, and HFE are shown in Table 4. (Charge / discharge test) Charge-discharge tests were carried out at 0.1 C. The results are shown in Table 4. The cycle characteristics are shown in Figure 6. The CV is shown in Figure 16.

[0185] Example 8 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated in the same manner as in Example 3. (Charge / discharge test) A charge-discharge test was carried out in the same manner as in Example 3, except that the lower limit of the cutoff voltage was set to 1.5 V and the upper limit was set to 3.0 V. The charge-discharge characteristics (1st, 2nd, and 30th cycles) are shown in Figure 8. The cycle characteristics are shown in Figure 9.

[0186] Example 9 (Building a lithium-sulfur battery) A lithium-sulfur battery was fabricated in the same manner as in Example 3. (Charge / discharge test) A charge-discharge test was carried out in the same manner as in Example 3, except that the lower limit of the cutoff voltage was set to 1.5 V and the upper limit was set to 3.5 V. The charge-discharge characteristics (first and second times) are shown in Figure 8. The cycle characteristics are shown in Figure 9.

[0187] [Table 4]

[0188] From Table 4, the example of this embodiment in which the first solvent is sulfolane has a significantly improved first coulombic efficiency compared to Comparative Example 2 in which the first solvent is tetraglyme. Also, from Table 4 and FIG. 6, it can be seen that the electrolyte composition of the example has a larger first discharge capacity and better cycle characteristics than the electrolyte composition of Comparative Example 1. That is, it can be seen that this embodiment has a high first coulombic efficiency, a large first discharge capacity, and better cycle characteristics. Also, from FIG. 9, it can be seen that the cycle characteristics are further improved when the lower limit of the cutoff voltage is set to 1.5 V. [Industrial Applicability]

[0189] The lithium-sulfur battery of the present embodiment has high first coulombic efficiency, large first discharge capacity, and excellent cycle characteristics, and has industrial applicability.

Claims

1. a positive electrode including a composite material including a porous carbon material and sulfur; a negative electrode containing lithium; The present invention includes an electrolytic solution including a first solvent having a sulfonyl group, a second solvent which is a fluorine-based solvent, and a lithium-containing electrolyte, The porous carbon material has a nitrogen content of 0.3% by mass or more and a specific surface area of ​​1000 m2 as determined by the BET method, which is a nitrogen adsorption / desorption method. 2 / g or more, and the pore volume obtained by quenched solid phase density function method (QSDFT) is 0.45 cm 3 / g or more, the first solvent is 1.0 to 8.0 mol per 1 mol of lithium in the lithium-containing electrolyte, the second solvent is one or more solvents selected from fluoroethylene carbonate (FEC) and 1,1,2,2-tetrafluoro-3-(1,1,2,2-tetrafluoroethoxy)-propane (HFE); The ratio of the second solvent is 0.2 to 1.5 mol per 1 mol of the first solvent. Lithium-sulfur battery.

2. 2. The lithium-sulfur battery of claim 1, wherein the first solvent is one or more solvents selected from sulfolane, 3-methylsulfolane, ethyl methyl sulfone, and ethyl isopropyl sulfone.

3. 3. The lithium-sulfur battery according to claim 1, wherein the sulfur content in the composite material is 35 to 90 mass%.

4. A method for producing a lithium-sulfur battery described in any one of claims 1 to 3, comprising an activation step of activating a nitrogen-containing carbon material to produce the porous carbon material, wherein the reduction rate of the nitrogen content in the activation step, defined by the following formula (I), is 30 to 99 mass%. Reduction rate of nitrogen content (mass%) = ((B-A) / B) x 100 (I) (In formula (I), A is the nitrogen content (mass%) in the porous carbon material measured by XPS, and B is the nitrogen content (mass%) in the nitrogen-containing carbon material measured by XPS.)

5. The method for producing a lithium-sulfur battery according to claim 4, wherein the nitrogen content in the nitrogen-containing carbon material is 2 to 45 mass%.

6. The method for producing a lithium-sulfur battery according to claim 4 or 5, wherein the activation is a chemical activation.

Citation Information

Patent Citations

  • Porous carbon material and method for producing the same, complex and method for producing the same, and positive electrode material for lithium sulfur batteries

    JP2018039685A

  • Lithium-sulfur battery

    WO2019049826A1